Hubungan Tingkat Pengetahuan Dan Sikap Dengan Perilaku Pencegahan Penularan HIV/AIDS Pada Pasangan ODHA Di Klinik Dahlia UPTD Puskesmas Bergas Tahun 2022: The Relationship Level Of Knowledge And Attitude With Prevention Behavior Of HIV/AIDS Transmission In Couples Of Plhiv In PLHIV In Dahlia Clinic Uptd Puskesmas Bergas, 2022 - Romsanah Romsanah; Heri Sugiarto; Sri Lestari (Universitas Ngudi Waluyo, 2023)
HIV/AIDS cases are like an iceberg phenomenon, where the number found is far lower than the actual number of sufferers. In Semarang Regency, the number of people living with HIV/AIDS in 2019 has increased compared to before. According to risk factors, Sero Discordant (one partner is HIV positive, while the other is not) is 92.19%, sex worker customers (PS) are 10.57%, and men who have sex with men (MSM) are 8.75%. This study aims to analyze the relationship between knowledge and attitudes toward HIV/AIDS transmission prevention behavior in PLHIV couples. The research design is the quantitative analytic cross-section sectional approach. The population was this study was at the Dahlia Clinic which had partners, totaling 33 people. The sample was taken as a total population, but there were 5 people who were not willing to be respondents, so that the sample was 28 people living with HIV/AIDS. The variables studied were knowledge, attitudes, and HIV/AIDS prevention behavior. Data collection was carried out using a questionnaire in the form of a google form. Data were analyzed descriptively and analytically. For the purposes of testing the hypothesis used fisher's exact test. From the research, the results for the variable knowledge of PLWHA were 23 respondents (82.10%) with a high level of knowledge and 5 respondents (17.90%) had a moderate level of knowledge. For the attitudes of PLWHA, 25 respondents (89.29%) had a positive attitude, while 3 respondents had a negative attitude (10.71%). There is no relationship between the level of knowledge and behavior to prevent HIV/AIDS transmission with a p-value of 0.29, nor is there a relationship between attitudes and behavior to prevent transmission of HIV/AIDS with a p-value of 1.00. It was concluded that the knowledge and attitude variables were not related to the behavior of preventing the transmission of HIV/AIDS in PLWHA partners. prevent transmission of HIV/AIDS with a p-value of 1.00. It was concluded that the knowledge and attitude variables were not related to the behavior of preventing the transmission of HIV/AIDS in PLWHA partners. Keywords: prevention, transmission, PLHIV, HIV/AIDS ABSTRAK Kasus HIV/AIDS seperti fenomena gunung es, dimana jumlah yang ditemukan jauh lebih rendah daripada jumlah penderita yang sebenarnya. Di Kabupaten Semarang, jumlah penderita HIV/AIDS tahun 2019 jumlahnya meningkat bila dibandingkan sebelumnya. Menurut faktor resikonya, Sero Discordant (salah satu pasangan adalah penderita HIV, sementara yang lain tidak) sebesar 92,19%, pelanggan Pekerja Seks (PS) sebesar 10,57%, Lelaki Seks Lelaki (LSL) 8,75%. Penelitian ini bertujuan untuk menganalisis hubungan pengetahuan dan sikap dengan perilaku pencegahan penularan HIV/AIDS pada pasangan ODHA. Desain penelitiannya yaitu analitik kuantititatif dengan pendekatan cross sectional. Populasi dalam penelitian ini adalah ODHA di Klinik Dahlia yang mempunyai pasangan, sebanyak 33 orang. Sampel diambil secara total populasi, namun ada 5 orang yang tidak bersedia menjadi responden, sehingga sampel didapatkan sebanyak 28 orang ODHA. Variabel yang diteliti yaitu pengetahuan, sikap, dan perilaku pencegahan HIV/AIDS. Pengumpulan data dilakukan dengan menggunakan kuesioner dalam bentuk google form. Data dianalisis secara deskriptif dan analitik. Untuk keperluan uji hipotesis digunakan uji fisher exact. Dari penelitian didapatkan hasil untuk variabel pengetahuan ODHA sebanyak 23 responden (82,10 %) dengan tingkat pengetahuan tinggi dan 5 responden (17,90%) memiliki tingkat pengetahuan sedang. Untuk sikap ODHA, didapatkan responden dengan sikap yang positif sebanyak 25 responden (89,29 %), sedangkan 3 responden mempunyai sikap negatif (10,71%). Tidak ada hubungan antara tingkat pengetahuan dengan perilaku pencegahan penularan HIV/AIDS dengan p value 0,29, juga tidak ada hubungan antara sikap dengan perilaku pencegahan penularan HIV/AIDS dengan p value 1,00. Disimpulkan bahwa variabel pengetahuan dan sikap tidak berhubungan dengan perilaku pencegahan penularan HIV/AIDS pada pasangan ODHA. Kata kunci : pencegahan, penularan, ODHA, HIV/AIDS